Creating Empowerment Communication Model: Case Study Of Community Dialogue Process - Gemiharto, Ilham; Yusup, Eka (Communica : Journal of Communication, 2023)
The challenges that communication practitioners face in empowering communities living near multinational companies are significant, especially in ensuring these communities receive their social rights from the profits generated by these companies. Often, mining companies show little concern for the environmental consequences of their exploration activities on affected communities. These qualitative case studies use various research methods, including observation, interviews, document analysis, and descriptive data analysis techniques, with beneficiaries and relevant officials as the primary informants. The core objective of this study is to build a model of communication empowerment through the process of community dialogue. This study focuses on the case of a geothermal exploration project in Kamojang, Garut, using a case study approach to explain the development of an empowerment-oriented communication model through dialogue. This analysis underscores the critical significance of addressing the participatory needs of marginalized communities. Communication models for community empowerment developed near mining company operations are essential in preparing these communities to be self-sufficient, even after the closure of exploration sites. The study not only emphasizes the urgent need to empower communities affected by the company's activities but also showcases practical models for achieving this empowerment through dialogue. It serves as a valuable blueprint for improving communication strategies in the same context, with potentially broader implications in corporate social responsibility and community development practices.